Arthroscopic Techniques and Anatomy of the Foot and Ankle A Surgical Atlas - Wei, Baofu; Yan, Alan Y.; Amendola, Annunziato; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This expansive, full-color atlas presents the detailed surgical anatomy and approaches for the most commonly performed arthroscopic procedures for the foot and ankle, including detailed descriptions of the equipment and operative set-up for successful arthroscopic procedures. Opening chapters discuss the relevant gross anatomy and instrumentation utilizing both cadaver and intraoperative photos, before proceeding into step-by-step presentations of nearly two dozen surgical procedures, from managing ankle instability and fractures and osteochondral lesions to peroneal tendon repair, plantar fascia release and joint arthrodesis. For each surgical procedure, indications and contraindications are provided, along with appropriate approaches and portals and possible complications. Each chapter is generously illustrated with relevant radiology and intraoperative and arthroscopic photos for maximum visual impact and ease of use, and includes a curated selection of suggested readings for further investigation. An excellent reference for foot and ankle surgeons at every skill level, Arthroscopic Techniques and Anatomy of the Foot and Ankle will be the go-to guide for years to come.
Gross Anatomy of Ankle Joint for Arthroscopy -- Arthroscopy Instruments and Application -- Anterior Arthroscopy of the Ankle Joint: General Principles and Arthroscopic Examination -- Posterior Arthroscopy of the Ankle and Subtalar Joint: General Principles and Arthroscopic Examination -- Osteochondral Lesions of Talus -- Osteochondral Lesions of the Tibial Plafond -- Anterior Ankle Impingement -- Chronic Ankle Instability -- High Ankle Sprain (Syndesmotic Injury) -- Arthroscopic-assisted treatment of Ankle Fracture -- Arthroscopic Ankle Arthrodesis -- Posterior Approach for Osteochondral Lesions of the Talus -- Posterior Ankle Impingement: Os Trigonum Syndrome -- Posterior Impingement: FHL Tendinopathy -- Arthroscopic Subtalar Joint Arthrodesis: Posterior Approach -- Arthroscopic Subtalar Joint: Lateral Approach -- Haglund$1 (Bs Deformity and Retrocalcaneal Bursitis -- Peroneal Tendon Disorders -- Endoscopic Gastrocnemius Recession -- Endoscopic Plantar Fascia Release -- Hallux Metatarsophalangeal (MTP) Joint Arthroscopy.s
Keywords: Orthopedics; Orthopaedics; Arthroscopy; Atlases